A century of bank rate - Hawtrey, R. G. (London : F. Cass, 1962)
It shows that the reliance on bank rate as an instrument of monetary policy had evolved through a century of experience, and that despite changes this experience was applicable to the problems of monetary policy.
Based on a series of three Alfred Marshall lectures, given at Cambridge in Nov. 1937.
Includes index
mf 22/01/2019
Loans
Keywords: Interest rates; Monetary policy; Currency question